Neutrophil extracellular traps: a novel contributor to vascular calcification in chronic kidney disease - Wang, Yan; Li, Wenjun; Liang, Yufeng; Wan, Jianxin (Frontiers in Immunology, 2025)
BackgroundAmong patients with chronic kidney disease (CKD), vascular calcification significantly contributes to cardiovascular health issues, though the underlying molecular mechanisms remain unclear. Recent research highlights neutrophil extracellular traps (NETs) as critical mediators of vascular damage and pro-calcific processes.MethodsWe obtained transcriptomic data from the NCBI GEO database for CKD rodent models and identified differentially expressed genes, selected genes using machine learning, functional enrichment, profiling of immune infiltration, transcription factor (TF) activity prediction and drug–gene interaction analysis.ResultsOur analysis revealed 36 NET-related genes with differential expression, and 19 were confirmed by the RobustRankAggreg method. Among them, Mmp12 and Comp emerged as the most consistently selected diagnostic markers across five machine learning algorithms, exhibiting excellent predictive performance (AUC > 0.95). These genes were enriched in neutrophil chemotaxis, ECM remodeling, and PI3K-Akt-mTOR signaling pathways. Immunohistochemistry confirmed NET deposition in calcified arteries of rat, and quantitative PCR and Western blot validated key NRGs expression in CKD rat aortae.ConclusionOur results demonstrate that NET-related genes may contribute to CKD-associated vascular calcification in rodent models. Specifically, this work provides evidence for a potential mechanistic link between NET biology and vascular calcification in CKD, thereby offering insights into immune-vascular interactions and raising the possibility of exploring NET-targeted approaches to mitigate vascular damage.